2017
DOI: 10.1016/j.chemosphere.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles induce oocyte maturation in zebrafish (Danio rerio)

Abstract: Public concern regarding silver nanoparticles (AgNPs) in the environment has been increasing since they can cause adverse effects in some aquatic species. However, few data are actually available on the effects of AgNPs on the germ cells. In the present study, we used the zebrafish ovarian follicle as a model to assess the potentially adverse effects of AgNPs on oocyte maturation (germinal vesicle breakdown, GVBD) in vitro. Similar to the maturation inducing hormone (17α, 20β-dihydroxy-4-pregnen-3-one), AgNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…The high fecundity rates of zebrafish are well suited to assessing the impact of agents on various aspects of reproduction, from egg production to fertilization rates to subsequent embryo viability. For example, reduced egg production and increased embryo mortality represent a hallmark of chronic exposure with TiO 2 NPs [ 37 ], while in contrast Ag NPs mediated enhanced maturation of zebrafish oocytes due to increased oxidative stress and resultant follicle cell apoptosis [ 38 ].…”
Section: Approaches For Measuring Nanoparticle Toxicity In Zebrafimentioning
confidence: 99%
See 1 more Smart Citation
“…The high fecundity rates of zebrafish are well suited to assessing the impact of agents on various aspects of reproduction, from egg production to fertilization rates to subsequent embryo viability. For example, reduced egg production and increased embryo mortality represent a hallmark of chronic exposure with TiO 2 NPs [ 37 ], while in contrast Ag NPs mediated enhanced maturation of zebrafish oocytes due to increased oxidative stress and resultant follicle cell apoptosis [ 38 ].…”
Section: Approaches For Measuring Nanoparticle Toxicity In Zebrafimentioning
confidence: 99%
“…Zebrafish have been utilized for a myriad of nanotoxicology studies [ 36 , 37 , 38 , 48 , 70 , 71 ]. A summary of key studies involving the analysis of metal, metal oxide and carbon-based nanoparticles, particularly those related to shape, size and surface charge are discussed below, with relative toxicity summarized ( Table 1 ).…”
Section: Selected Nanotoxicology Studies In Zebrafishmentioning
confidence: 99%
“…Additionally, studies provided evidence that the toxicity to oocytes increased with the silver molar fraction [ 31 - 33 ]. An in vitro model of zebrafish ovarian follicle cells surrounding an oocyte, thecal cells and granulosa cells exhibited apoptosis with phenotypes of irregular cell morphology, disorganized cytoplasm and fragmented and condensed nuclei after exposure to Ag NPs (30 mg/mL) and AgNO 3 (10 mg/mL) [ 34 ]. In vitro experiments also showed that quantum dot-transferrin (QD-Tf) bioconjugates were mostly taken up by the cumulus cells, but no QDs entered the oocytes.…”
Section: Toxicity Of Nps In Oogenesismentioning
confidence: 99%
“…Histologic examinations revealed that empty follicular structures were formed within the ovary tissue. Chen et al [25] reported that silver nanoparticles (used in biosensors, chemical sensors, cosmetics industry, medicine and the paint industry) induce oocyte maturation in zebrafish, promote apoptosis in follicular cells surrounding the oocyte, induce germinal vesicle breakdown, decrease cAMP concentration and cause apoptosis of ovarian follicle cells. Paraptosis has been characterized by chromatin condensation, cytoplasmic vacuolization with many small vacuoles created in the cytoplasm, the widening of the perinuclear space, mitochondrial vesiculation and mitochondrial swelling [26,27].…”
Section: Discussionmentioning
confidence: 99%